ANALISIS DIAGNOSTIK KESULITAN BELAJAR STATISTIKA MAHASISWA BKI PADA FAKULTAS USHULUDDIN ADAB DAN DAKWAH IAIN PALU - Karmawati Karmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
This study aims to know the students` learning difficulties of descriptive statistics; know the factors that cause learning difficulties of descriptive statistics BKI student at Ushuluddin Adab and Da`wah Faculty IAINPalu. This study uses descriptive quantitative approach with research subjects are BKI students at Ushuluddin Adab and Da`wah Faculty IAINPalu. Data collection techniques were used tests and interviews. The research instrument used is a diagnostic test and interview guidelines. Data analysis technique used is descriptive statistics. The results showed that students learning difficulties statistical average of 80.06% and in the category of